Zyklus, Refrain, Kontakte - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1960)
ZYKLUS / CYCLE for a percussionistREFRAIN for three playersKONTAKTE / CONTACTS for electronic sounds, piano and percussion